The impact of tumor size on the association of the extent of lymph node resection and survival in clinical stage I non-small cell lung cancer. Issue 3 (December 2015) - Gulack, Brian C.; Yang, Chi-Fu Jeffrey; Speicher, Paul J.; Meza, James M.; Gu, Lin; Wang, Xiaofei; D'Amico, Thomas A; Hartwig, Matthew G.; Berry, Mark F.
Highlights: We analyzed patients with stage I NSCLC in the NCDB. We evaluated the association of the extent of lymph node evaluation and survival. More extensive lymph node evaluations were associated with improved survival. However, the optimal number of lymph nodes evaluated depended on tumor size. Policy should not dictate a lymph node evaluation cut-off among patients with resectable NSCLC. Abstract: Introduction: Lymph node evaluation for node-negative non-small cell lung cancer (NSCLC) is associated with long-term survival but it is not clear if smaller tumors require as extensive a pathologic nodal assessment as larger tumors. This study evaluated the relationship of tumor size and optimal extent of lymph node resection using the National Cancer Data Base (NCDB). Materials and methods: The incremental survival benefit of each additional lymph node that was evaluated for patients in the NCDB who underwent lobectomy for clinical Stage I NSCLC from 2003 to 2006 was evaluated using Cox multivariable proportional hazards regression modeling. The impact of tumor size was assessed by repeating the Cox analysis with patients stratified by tumor size ≥2 cm vs <2 cm. Results: A median of 7 [interquartile range: 4, 11] lymph nodes were examined in 13, 827 patients who met study criteria. Following adjustment, the evaluation of each additional lymph node demonstrated a significant survival benefit through 11 lymph nodes. After grouping patients by tumor size, patients with tumors <2 cm demonstrated a significant survival benefit for the incremental resection of each additional lymph node through 4 lymph nodes while patients with tumors ≥2 cm had a significant survival benefit through 14 lymph nodes. Conclusion: Pathologic lymph node evaluation is associated with improved survival for clinically node-negative NSCLC, but the extent of the necessary evaluation varies by tumor size. These results have implications for guidelines for lymph node assessment as well as the choice of surgery vs other ablative techniques for clinical stage I NSCLC.